The Importance of Islamic Values in the Early Childhood Education Curriculum: A Character Education Approach - Arsyad, Lukman (Journal La Edusci, 2023)
The influence of incorporating Islamic beliefs into the early childhood education (ECE) curriculum on social skills, cultural identity, and moral development is investigated in this study. Based on a qualitative examination of questionnaires, classroom observations, and interviews with educators, parents, and caregivers, our findings highlight the advantages that people believe to come from increased cultural identification and improved moral development. Despite obstacles, innovative approaches were found, most notably parental participation and community engagement. Improvements in social skills and a more profound comprehension of values were noted. Cultural sensitivity became apparent, highlighting the importance of inclusive content and tolerance for a range of viewpoints. This study offers useful information to help educators and legislators create an ECE environment that is ethically sound and sensitive to cultural differences.